Blood, Sweat and Dummy Tummies: Kin Labour and Transnational Surrogacy in India - Pande, Amrita (Anthropologica, 2015)
How do the actors involved in transnational surrogacy negotiate anxieties about global inequities that underpin these services? In this ethnography of transnational surrogacy in India, I analyze what I call the "kin labour" done by the Indian surrogates and the (often international) intended mother to downplay these anxieties. Kin labour includes the labour of forging ties with the baby as well as forming ties of sisterhood, sending gifts, and writing letters to intended mothers. I argue that while at one level this kin labour sustains relationships beyond contracts and across borders of race, class and nationality, at another level it ultimately reifies structural inequalities within transnational contractual surrogacy.